2014
DOI: 10.1249/mss.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Lowering of Fetuin-A May Increase Hepatic Insulin Sensitivity

Abstract: Introduction Fetuin-A is a novel hepatokine, and there is preliminary evidence that it may contribute to the pathogenesis of type 2 diabetes. Exercise reduces fetuin-A, but the specific metabolic effects particularly as they relate to the regulation of insulin resistance are unknown. This led us to examine the effect of exercise training on circulating fetuin-A in relation to skeletal muscle and/or hepatic insulin resistance in obese adults. Methods Twenty older adults (66.3 ± 0.9 yr; body mass index, 34.1 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 27 publications
5
52
1
Order By: Relevance
“…Although it has been demonstrated that exercise may reduce plasma fetuin‐A concentrations (Malin et al. ), and that interaction of fetuin‐A and FFAs can induce TLR4‐associated insulin resistance (Pal et al. ; Stefan and Haring ), we seem to be the first to demonstrate that changes in fetuin‐A and FFAs together may predict some of the benefits seen on insulin sensitivity after long‐term exercise.…”
Section: Discussionmentioning
confidence: 54%
“…Although it has been demonstrated that exercise may reduce plasma fetuin‐A concentrations (Malin et al. ), and that interaction of fetuin‐A and FFAs can induce TLR4‐associated insulin resistance (Pal et al. ; Stefan and Haring ), we seem to be the first to demonstrate that changes in fetuin‐A and FFAs together may predict some of the benefits seen on insulin sensitivity after long‐term exercise.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have also shown that exercise alone , hypocaloric diets , gastric banding or bypass surgery , and medication exert beneficial effects and alter insulin sensitivity. Among older adults, a 12‐week supervised exercise training was shown to lower serum Fet‐A by 8%, which was correlated with hepatic insulin resistance and high‐molecular‐weight adiponectin . Further, a 16‐month longitudinal study of 75 patients with morbid obesity after gastric bypass demonstrated that changes of serum Fet‐A were significantly correlated with changes in fasting insulin, 2‐hour insulin, and HOMA‐IR .…”
Section: Discussionmentioning
confidence: 95%
“…Gastric bypass surgery that resulted in a 35% body weight loss decreased serum Fet‐A, which correlated with fasting insulin, postprandial insulin, and homeostasis model assessment of insulin resistance (HOMA‐IR) . High‐intensity exercise has led to significantly decreased serum Fet‐A, which is associated with lower hepatic insulin resistance .…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with work by Harnisch et al who found no difference on post-surgery weight loss or disease resolution of T2D and hypertension at 12 and 24 months between patients with approximate 10 pound weight gain compared with those who lost 10 pounds preoperatively (19) . Thus, preoperative weight loss was not necessarily correlated with greater BMI change postoperatively, and more work is required to determine if optimizing cardiorespiratory fitness, with or without weight loss, can promote long term weight maintenance, insulin sensitivity and cardio-metabolic health (20, 21) .…”
Section: Discussionmentioning
confidence: 99%